Model of Steady State Cyclohexane Oxidation for Ketone-Alcohol (K-A) Oil Production - Agustriyanto, Rudy; Fatmawati, Akbarningrum (Makara Journal of Science, 2014)
Cylohexane oxidation is of great industrial importance in the production of intermediates for the manufacture of nylon6 and nylon-6,6. Most cyclohexane is commercially converted into a cyclohexanone–cyclohexanol mixture (known as K-A oil) by catalytic oxidation. K-A (Ketone-Alcohol) oil is then used as a raw material for adipic acid and caprolactam production. Practically, if the cyclohexanol content of KA oil is higher than that of cyclohexanone, it is more profitable to convert it into adipic acid; otherwise caprolactam production is more likely. The steady state cyclohexane oxidation reaction model in a stirred tank reactor for K-A oil production is presented and solved in this paper. The model was derived based on the mass balance and mass transfer equations using the kinetic equation. The set of algebraic equations was solved using non linear programming. The advantage of this method is that the relationship among variables can be better understood and an appropriate solution to the equation set can be obtained more quickly. Simulation results are particularly useful for process design such as in determining reactor dimensions and operating conditions.